SIMULATION OF THE RECIPE COMPOSITION OF HEALTHY FOOD PRODUCTS BASED ON FUNCTIONAL COMPOSITIONS - ANTONENKO, Аrtem; BROVENKO, Tetiana; KRYVORUCHKO, Myroslav; STUKALSKA, Nataliya; TOLOK, Galina; TONKYKH, Oleksii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article provides justification and development of the methodology for modeling the recipe composition of health food products based on functional compositions. The basis of the modeling is the principle of food combinatorics, which consists in the justified quantitative selection of the main raw materials and food additives, which together ensure the formation of the necessary organoleptic and physicochemical properties, the given level of nutritional (food, biological) and energy value. Modeling of food products is the process of creating a product as a single integrated system consisting of elements that do not individually provide the specified properties. Conceptual approaches to the modeling of functional compositions and products based on them consist in optimizing the selection and ratio of ingredients, by which it is possible to obtain a composition that, in terms of quantitative content and qualitative composition, best meets the indicators of nutritional value and medical and biological requirements. The application of a mathematical apparatus based on the formalization of qualitative and quantitative indicators of the composition, nutritional value of individual ingredients and their combinations in the composition of model functional compositions allows, through simulation modeling, to determine the total content of an individual component. Taking into account the above-mentioned factors, the modeling results, as a rule, provide effective optimization of the product composition and parameters of individual operations of the technological process. Upon completion of the stage of multi-level experimental modeling, the functional compositions and technologies of the products are checked in laboratory and production conditions, after which their final adjustment is made. At the final stage, comprehensive studies of the main indicators of the quality of finished products, calculation of economic indicators, testing of technology in production conditions, preparation, coordination and approval of regulatory documents and organization of industrial implementation are carried out. The application of the design methodology of model functional compositions and food products allows to increase the degree of use of raw materials and expand the assortment of products with a given composition and properties for health purposes.
Keywords: model compositions; functional compositions; protein; fats; carbohydrates; macro- microelements; vitamins; energy value